Electronic properties of Al/p-Si/C70/Au MIS-type diode - Gedikpinar, M.; Cavas, M.; Alahmed, Zayed A.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
The electrical characteristics of the Al/p-Si/C-70/Au diode were investigated by current-voltage and capacitance-voltage measurements. The current-voltage characteristics confirm that the diode is a metal-insulator semiconductor type device. The decrease in ideality factor and increase in barrier height values of the diode were observed with temperature. This behavior was explained on the basis of Schottky barrier height inhomogeneities. The zero-bias mean barrier height (phi) over bar (bo), and Richardson values for the diode were found to be 1.06 eV and 33.12 A/cm(2) K-2, respectively. The obtained Richardson constant (A* = 33.12 A/cm(2) K-2) is in agreement with the theoretical value of A* = 32 A/cm(2) K-2. The interface state density properties of the diode were analyzed and the shape of the interface state density is changed with temperature. The phi(B) value obtained from C-V measurement is higher than that of phi(B) value obtained from I-V measurements. The discrepancy between phi(B)(C-V) and phi(B)(I-V) values was explained by distribution of Schottky barrier height due the inhomogeneities. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Organic semiconductor; MIS diode; Interface states